A comparison study on electromagnetic susceptibility of current reference circuits with scaling-down technologies and schemes. (November 2020) - Wang, Zhian; Li, Binhong; Wu, Jianfei; Zhao, Wenxin; Li, Bo; Liu, Hainan; Guan, Chongjie; Feng, Shiwei; Luo, Jiajun; Ye, Tianchun
Abstract: This paper studies the effects of process node and circuit schemes on the electromagnetic susceptibility (EMS) of current reference circuits. Three reference circuits using PDSOI with technology node of 0.5 μm (VREF50), 0.35 μm (VREF33) and 0.18 μm (VREF18) are used. VREF50 has an additional CASCODE structure to achieve a PSRR enhancement. The test results show that when the electromagnetic interference (EMI)is injected into the terminals VDD and VSS, the reference currents in both of the three circuits exhibit a negative shift. The main reason is that the drain voltage of the transistor close to the terminal VDD fluctuates greatly, causing a deviation from the saturation to the linear region from time to time, hence reducing the average value of the current. The higher voltage margin with the large process node, the stronger the immunity of the reference circuit to EMI. It is worth noting that the CASCODE structure has a negative effect on low frequency large-signal EMI. Therefore, VREF50 and VREF33 have the similar EMS. In a higher frequency range, the parasitic effect brought by the CASCODE structure becomes more serious, which increases the high-frequency impedance of the circuit. Finally, simulation results imply that the immunity level is improved by decreasing bypass capacitor between the sensitive node and the VDD to reduce the EMI injection, and replacing the nonlinear device by a positive temperature coefficient resistor to improve the circuit linearity. Highlights: The failure mechanism of current reference in EMI is investigated. The coupling path of current reference to EMI is analyzed by simulation. The scaling-down technology has significant influence on EMS of current reference. Two suggestions are put forward to improve the immunity to EMI by simulation. The influence of CASCODE on EMS of current reference is related to frequency.